Optical assay for biotechnology and clinical diagnosis - Moczko, Ewa; Cauchi, Michael; Turner, Claire; Meglinski, Igor V.; Piletsky, Sergey A. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
In this paper, we present an optical diagnostic assay consisting of a mixture of environmental-sensitive fluorescent dyes combined with multivariate data analysis for quantitative and qualitative examination of biological and clinical samples. The performance of the assay is based on the analysis of spectrum of the selected fluorescent dyes with the operational principle similar to electronic nose and electronic tongue systems. This approach has been successfully applied for monitoring of growing cell cultures and identification of gastrointestinal diseases in humans.